Pedological origin and edaphic factors drive biota in vineyard soils of Northeast Italy - Raffaella Morelli; Roberto Zanzotti; Massimo Pindo; Claudio Donati; Alessandro Cestaro; Emanuela Coller (OENO One)
Soil biota is responsible for essential biological processes occurring in the soil. Biota composition, biodiversity and activity can be affected by soil properties, biogeography and human activities. This study, conducted in vineyards of Northeast Italy, aimed to understand the combined effect of edaphic and agronomic factors on the composition and biodiversity of soil biota in four soil types characterised by different pedological origin. The soil biota was studied by simultaneously investigating the composition and the biodiversity of fungal, bacterial and microarthropod communities and their interactions with abiotic factors. The results show that the impact of natural soil characteristics and viticulture activity on biota depends on soil type. Some fungal, bacterial and microarthropod community groups were characteristic only of certain soil types. Geographical position and edaphic factors mainly affected the composition of microbial communities, while microarthropods seemed to respond less to these variables. Depending on the origin of the soil, the biodiversity of the biota responded differently to viticulture practices. The study shows that understanding how natural and agronomic factors drive soil biota makes it possible to predict the effect of natural or artificial changes on soil biological processes.